Strongylocentrotus nudus Eggs Polysaccharide Enhances Macrophage Phagocytosis Against E.coli Infection by TLR4/STAT3 Axis - Tian, Xinlei; Guo, Min; Zhang, Xiaoya; Guo, Lingfeng; Lan, Nan; Cheng, Yaojun; Han, Yannan; Wang, Mingxin; Peng, Zhonglu; Zhou, Changlin; Fan, Hongye (Frontiers in Pharmacology, 2022)
Antibiotics resistance is one of the most significant public health threats globally. Strategies that strengthening host defenses to control pathogens infection have become a hot research field. Macrophage exerts early host defense activities through activated host pattern recognition receptors (PRRs), such as Toll-like receptor 4 (TLR4), facilitating phagocytosis and elimination of invading pathogens. However, few activators of PRRs have been approved for clinical use because of their toxic effects. This study aimed to investigate whether Strongylocentrotus nudus eggs polysaccharide (SEP), a non-toxic extract from seafood, contributes to host defense against bacterial infection. Results showed that SEP promoted bacterial clearance by enhancing phagocytosis of macrophage during E.coli infection in vitro, while inhibited by TLR4 specific inhibitor TAK-242, STAT3 inhibitor Stattic or blockade of CD64. In addition, SEP protected mice from E.coli induced mortality, reduced pulmonary inflammation and inhibited dissemination of bacteria to organs, while TAK-242 retarded the protection of SEP. Overall, SEP strengthened innate host defense and improved the outcome in bacterial infection, suggesting that SEP could be used as a potential immunomodulator in host-directed therapies.